A kind of anti-aging PVC material and its preparation method and application

By adding 4A zeolite, nanotitanium dioxide, alkaline magnesium sulfate whiskers and other components to the PVC material, the problem of decomposition of PVC material during high temperature or long-term exposure to the sun is solved, which significantly improves its thermal stability and light resistance stability, extends its service life and broadens its application range.

CN119119669BActive Publication Date: 2025-03-14BAIN MEDICAL EQUIPMENT (GUANGZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411588236.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

PVC materials will decompose during high temperatures or long-term exposure to the sun, producing hydrogen chloride, resulting in discoloration, degradation of mechanical properties, short service life and limited application range.

Method used

An anti-aging PVC material is used, including PVC or PMMA grafted PVC, plasticizer, stabilizer, 4A zeolite, nanotitanium dioxide or PMMA modified nanotitanium dioxide, basic magnesium sulfate whiskers or PMMA modified basic magnesium sulfate whiskers and compatibility agents. Through the synergistic effect of these components, the thermal stability and light resistance of the material are improved.

Benefits of technology

It significantly improves the thermal stability and light resistance of PVC materials, extends service life, broadens the application range, and maintains good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of PVC materials, and specifically discloses an anti-aging PVC material and a preparation method and application thereof. The anti-aging PVC material of the present invention comprises the following components in parts by weight: 100 parts of PVC or PMMA-grafted PVC, 3-20 parts of plasticizer, 2-5 parts of stabilizer, 0.5-5 parts of 4A zeolite, 1-3 parts of nano titanium dioxide or PMMA-modified nano titanium dioxide, 0.1-1.5 parts of basic magnesium sulfate whisker or PMMA-modified basic magnesium sulfate whisker, 0.2-2 parts of compatibilizer, and 0-5 parts of other additives. The present invention cooperates with 4A zeolite, nano titanium dioxide, basic magnesium sulfate whisker and compatibilizer to synergistically improve the anti-aging performance of PVC materials on the basis of maintaining good mechanical properties of the materials, so as to improve the service life of PVC materials and broaden their application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of PVC materials, and in particular relates to an anti-aging PVC material and a preparation method and application thereof. Background Art

[0002] PVC (polyvinyl chloride) has good mechanical properties, solvent resistance, flame retardancy, and is easy to process and shape; it has an amorphous structure, but it will decompose and produce hydrogen chloride at high temperatures (above 100°C) or long-term exposure to the sun, and will further decompose through internal autocatalysis, eventually causing it to change color and rapidly decline in mechanical properties, affecting its continued use. Therefore, it is urgent to improve the light, heat and other environmental aging properties of PVC materials to extend their service life and broaden their scope and prospects for application. Summary of the invention

[0003] In view of the problem that the PVC material involved in the above-mentioned prior art has poor anti-aging performance, the present invention provides an anti-aging PVC material and a preparation method and application thereof. The PVC material of the present invention has good anti-aging performance and can solve the problem that PVC is not resistant to heat and light.

[0004] In order to achieve the above-mentioned purpose, the present invention provides an anti-aging PVC material, comprising the following components in parts by weight: 100 parts of PVC or PMMA-grafted PVC, 3-20 parts of plasticizer, 2-5 parts of stabilizer, 0.5-5 parts of 4A zeolite, 1-3 parts of nano titanium dioxide or PMMA-modified nano titanium dioxide, 0.1-1.5 parts of basic magnesium sulfate whisker or PMMA-modified basic magnesium sulfate whisker, 0.2-2 parts of compatibilizer, and 0-5 parts of other additives.

[0005] In the system of the present invention, when 4A zeolite, nano titanium dioxide and basic magnesium sulfate whisker coexist, the thermal stability and light resistance stability of the material can be significantly increased. At the same time, 4A zeolite, nano titanium dioxide and basic magnesium sulfate whisker are inorganic fillers, and the compatibility of the three with the PVC matrix is ​​relatively good. In addition, the system contains a compatibilizer, and the tensile strength of the material will not be significantly reduced. Among them, 4A zeolite has a porous structure and is weakly alkaline, which can significantly neutralize and absorb HCl in the system; nano titanium dioxide has an absorption effect on ultraviolet light, and it is a nanostructure, which is more The surface energy is high, and it has a certain adsorption effect on free radicals, HCl and other substances therein, and can significantly inhibit the decomposition of PVC as a whole; the basic magnesium sulfate whisker is weakly alkaline and has a fibrous structure, which can neutralize HCl, and its fibrous structure can play a role in strengthening and toughening; it may be that nano-titanium dioxide, 4A zeolite, and basic magnesium sulfate whiskers are synergistically interspersed in the PVC matrix to form a specific skeleton structure, which can not only synergistically improve the light and thermal stability of the material, but also will not cause a significant decrease in the toughness and strength of the material, and can still maintain good mechanical properties. In addition, PMMA has good compatibility with PVC. Grafting PMMA on PVC and / or modifying titanium dioxide and / or basic magnesium sulfate whiskers with PMMA can further improve the compatibility between the components, so as to achieve the purpose of improving the anti-aging properties of the material on the basis of the material having good mechanical properties.

[0006] In the system of the present invention, there is no particular limitation on the specific type of PVC, and pure PVC, graft-modified PVC, etc. can be used. The PVC can be selected to have a polymerization degree greater than 100, and more specifically, a polymerization degree of 500-100.

[0007] Preferably, the grafting rate of PMMA in the PMMA-grafted PVC is 1-10wt.%, specifically 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0008] Preferably, the preparation method of PMMA-grafted PVC comprises the following steps: melt-extruding a mixture of PVC powder and methyl methacrylate (MMA) at 150-180°C.

[0009] After PMMA grafting, the PVC matrix can significantly improve the tensile strength and anti-aging properties of the material.

[0010] Preferably, the specific surface area of ​​the 4A zeolite is 50-1000m 2 / g, specifically 50m2 / g, 200m 2 / g, 400m 2 / g, 600m 2 / g、800m 2 / g、1000m 2 / g, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0011] Preferably, the mass ratio of the nano titanium dioxide or PMMA-modified nano titanium dioxide to the basic magnesium sulfate whisker or PMMA-modified basic magnesium sulfate whisker is (1-1.8): (0.4-1.2), specifically 1:0.4, 1:0.8, 1:1.2, 1.5:0.4, 1.5:0.8, 1.5:1.2, 1.8:0.4, 1.8:0.8, 1.8:1.2, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0012] The mass ratio of basic magnesium sulfate whiskers to nano-titanium dioxide affects the coordination effect of nano-titanium dioxide, 4A zeolite, and basic magnesium sulfate whiskers in the system, and further affects the photothermal stability and tensile strength of the material. The inventors of the present invention have found that when the mass ratio of basic magnesium sulfate whiskers to nano-titanium dioxide is (0.4-1.2): (1-1.8), the material of the present invention has better anti-aging performance and tensile strength.

[0013] Preferably, the average particle size of the nano titanium dioxide is 100-1000nm, specifically 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0014] The average particle size of nano-titanium dioxide affects the effect of its dispersion in the matrix and interspersed in the skeleton structure formed by 4A zeolite and basic magnesium sulfate whiskers, and further affects the anti-aging effect and tensile strength of the material. The inventors of the present invention have found that when the average particle size of nano-titanium dioxide is 150-900nm, the anti-aging and tensile strength of the material can be further improved.

[0015] Preferably, the preparation method of PMMA-modified nano-titanium dioxide comprises the following steps:

[0016] (1) immersing nano titanium dioxide in an aqueous solution of cycloalkyl imidazoline quaternary ammonium salt and performing a surface modification reaction at 100-120° C. to obtain surface-modified nano titanium dioxide;

[0017] (2) The surface-modified nano-titanium dioxide, methyl methacrylate and methyl vinyl ketone are reacted under ultraviolet light to obtain PMMA-modified nano-titanium dioxide.

[0018] Preferably, in step (1), the concentration of the cycloalkylimidazoline quaternary ammonium salt aqueous solution is 1-10 wt.%.

[0019] Preferably, in step (1), the surface modification reaction time is 1-5 hours.

[0020] Preferably, in step (2), the mass ratio of the surface-modified nano-titanium dioxide, methyl methacrylate and methyl vinyl ketone is (400-600):(100-200):(1-5).

[0021] Preferably, in step (2), the reaction temperature is 50-70°C.

[0022] After PMMA grafting, nano-titanium dioxide can improve the compatibility between nano-titanium dioxide and the matrix, which not only improves the anti-aging performance of the material to a certain extent, but also enables the material to maintain better tensile strength.

[0023] Preferably, the preparation method of the PMMA-modified basic magnesium sulfate whisker comprises the following steps:

[0024] (1) drying the basic magnesium sulfate whiskers, grinding them, and dispersing them in water to obtain a basic magnesium sulfate whisker slurry;

[0025] (2) dissolving PMMA and calcium stearate in anhydrous ethanol and toluene solvents; then adding the basic magnesium sulfate whisker slurry to react under light-proof conditions, and then filtering and drying to obtain PMMA-modified basic magnesium sulfate whiskers.

[0026] Preferably, in step (1), the mass ratio of PMMA to calcium stearate is 1:(0.1-0.5).

[0027] Preferably, in the anhydrous ethanol and toluene solvents in step (2), the volume ratio of anhydrous ethanol to toluene is (1-5):1.

[0028] Preferably, in step (2), the reaction temperature is 60-90° C., and the reaction time is 20-60 min.

[0029] Preferably, in step (2), the stirring rate of the reaction is 100-500 rpm.

[0030] After the basic magnesium sulfate whiskers are grafted with PMMA, the compatibility of the basic magnesium sulfate whiskers with the matrix can be improved, which not only improves the anti-aging performance of the material to a certain extent, but also enables the material to maintain a better tensile strength.

[0031] Preferably, the compatibilizer is a maleic anhydride grafted compatibilizer.

[0032] Further preferably, the maleic anhydride grafted compatibilizer includes at least one of maleic anhydride grafted acrylonitrile-butadiene-styrene (ABS-g-MAH), maleic anhydride grafted polyethylene (PE-g-MAH) and maleic anhydride grafted polypropylene (PP-g-MAH).

[0033] Compatibilizers can significantly improve the compatibility between components in the system and the coordination between components. They can not only increase the anti-aging properties of the material to a certain extent, but also significantly improve the tensile strength of the material.

[0034] Preferably, the stabilizer includes at least one of an organic tin stabilizer, an organic zinc stabilizer, and an organic calcium stabilizer.

[0035] Preferably, the organic tin stabilizer includes at least one of di-n-octyltin dilaurate, tin methyl mercaptan, dibutyltin bis(butyl maleate), and di(β-butoxycarbonylethyl)tin di(isooctylthioacetate).

[0036] On the one hand, the stabilizer can absorb HCl released by the thermal degradation of PVC, and on the other hand, it can eliminate unstable chlorine atoms and other substances in the system, thus achieving a passivation effect and thus improving the stability of PVC.

[0037] Preferably, the plasticizer includes at least one of phthalate esters and epoxy plasticizers.

[0038] Preferably, the phthalate ester includes dioctyl phthalate, diisononyl phthalate and diisodecyl phthalate, and at least one of diisononyl phthalate and diisodecyl phthalate.

[0039] Adding a certain amount of plasticizer to the system of the present invention can improve the toughness, tensile strength and weather resistance of the material and improve the comprehensive performance of the material.

[0040] Preferably, the other additives include the following components in parts by weight: 0.1-2 parts of colorant, 0.1-5 parts of flame retardant, and 0.1-3 parts of lubricant.

[0041] Preferably, the lubricant includes at least one of polyethylene wax, oxidized polyethylene wax, stearic acid, butyl stearate, stearic acid monoglyceride, stearic acid alcohol, stearyl stearate, oleic acid monoglyceride, and ricinoleic acid monoglyceride.

[0042] The present invention can also add some other additives, such as colorants, flame retardants, etc., to improve the comprehensive performance of the material.

[0043] The present invention also provides a method for preparing the anti-aging PVC material, comprising the following steps: uniformly mixing, melt-kneading and extruding the raw materials in sequence to obtain the anti-aging PVC material.

[0044] Preferably, the temperature of the melt kneading is 160-200°C.

[0045] The present invention also provides an application of the anti-aging PVC material in the preparation of medical devices, which can specifically include the preparation of artificial dialyzers, blood oxygenators, blood separators, anesthesia evaporators and other equipment.

[0046] Compared with the prior art, the present invention has the following beneficial effects: the present invention cooperates with 4A zeolite, nano titanium dioxide, basic magnesium sulfate whiskers and a compatibilizer to synergistically improve the anti-aging properties of PVC materials while maintaining good mechanical properties of the materials, thereby increasing the service life of PVC materials and broadening their application scenarios. DETAILED DESCRIPTION

[0047] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0048] PVC: S-60, Formosa Plastics Ningbo, degree of polymerization 780±30.

[0049] PMMA (polymethyl methacrylate) grafted modified PVC: A mixture of PVC powder (S-60, Formosa Plastics Ningbo, degree of polymerization 780±30) and methyl methacrylate (MMA) was added into an extruder and melt-extruded at 150°C, wherein the screw speed was 40 rpm, and MMA accounted for 7% of the total mass of PVC and MMA.

[0050] Plasticizer: dioctyl phthalate (DOP), Shandong Beisu Chemical Industry.

[0051] Stabilizer: Calcium stearate and zinc stearate in a mass ratio of 1:1, commercially available.

[0052] 4A zeolite: Specific surface area about 600g / cm 2 , the average particle size after sieving is 2μm, Wuhan Jiyesheng Chemical Co., Ltd.

[0053] Nano-titanium dioxide 1: average particle size after sieving is 500 nm, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0054] Nano-titanium dioxide 2: the average particle size after sieving is 900 nm, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0055] Nano titanium dioxide 3: average particle size after sieving is 150nm, Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0056] Preparation method of modified nano titanium dioxide:

[0057] (1) immersing nano-titanium dioxide in a cycloalkyl imidazoline quaternary ammonium salt aqueous solution (5 wt.%) and performing surface modification at 110° C. for 3 h to obtain surface-modified nano-titanium dioxide;

[0058] (2) Surface-modified nano-titanium dioxide, methyl methacrylate and methyl vinyl ketone (mass ratio 500:180:2.5) were reacted at 60°C under ultraviolet light for 3 hours, and then dispersed and aged in ventilation (nitrogen) and dried for 12 hours to obtain polymethyl methacrylate-coated nano-titanium dioxide.

[0059] According to the above method, the above nano titanium dioxide 1, nano titanium dioxide 2, and nano titanium dioxide 3 are used as raw materials to prepare modified nano titanium dioxide 1, modified nano titanium dioxide 2, and modified nano titanium dioxide 3, respectively.

[0060] Basic magnesium sulfate whiskers: average diameter <1μm, average length 10-60μm, aspect ratio >30, Songzi Honglin Magnesium Materials Co., Ltd.

[0061] Preparation method of modified basic magnesium sulfate whisker:

[0062] (1) drying the basic magnesium sulfate whiskers, grinding them for 5 minutes, and dispersing them in water to obtain a basic magnesium sulfate whisker slurry;

[0063] (2) dissolving PMMA and calcium stearate (the mass ratio of PMMA to calcium stearate is 1:0.2) in anhydrous ethanol and toluene solvent (the volume ratio of anhydrous ethanol to toluene is 3.5:1);

[0064] (3) Adding basic magnesium sulfate whisker slurry under light-proof conditions, stirring at 80° C. and 350 r / min for 45 min to react, and then filtering and drying to obtain modified basic magnesium sulfate crystals.

[0065] Compatibilizer: ABS-g-MAH, Dongguan Shengli New Materials Co., Ltd.

[0066] Lubricant: Polyethylene wax, commercially available.

[0067] Example 1

[0068] A method for preparing an anti-aging PVC material in this embodiment includes the following steps:

[0069] (1) According to the raw material ratio in Table 1-2, the components except basic magnesium sulfate whiskers are mixed uniformly;

[0070] (2) Mixing is continued in an open mixer, and basic magnesium sulfate whiskers are added and mixed to form sheets (temperature is 150-180°C), and then pressed (170°C) into 2 mm thick long sheets through a press mold.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that this embodiment uses unmodified PVC, and the rest is the same.

[0073] Embodiment 3-4

[0074] Compared with Example 1, Example 3-4 differs in that the total weight of the modified basic magnesium sulfate whisker and the modified nano-titanium dioxide is the same, but the mass ratio of the modified basic magnesium sulfate whisker and the modified nano-titanium dioxide is different, and the rest are the same.

[0075] Embodiment 5-6

[0076] Compared with Example 1, the difference between Example 5-6 is that the total weight of the modified basic magnesium sulfate whisker and the modified nano-titanium dioxide is different, and the rest is the same.

[0077] Embodiment 7-8

[0078] Compared with Example 1, the difference between Example 7-8 is that the average particle size of titanium dioxide used in the modified titanium dioxide is different, and the rest is the same.

[0079] Example 9

[0080] The present embodiment is different from the embodiment 1 in that the nano titanium dioxide in the present embodiment is not modified by PMMA, and the rest is the same.

[0081] Example 10

[0082] The present embodiment is different from the embodiment 1 in that the basic magnesium sulfate whiskers of the present embodiment are not modified by PMMA, and the rest are the same.

[0083] Examples 11-12

[0084] The difference between Examples 11-12 and Example 1 is that the weight proportion of 4A zeolite is different.

[0085] Examples 13-14

[0086] The difference between Examples 13-14 and Example 1 is that the weight proportion of the compatibilizer is different.

[0087] Comparative Example 1

[0088] Compared with Example 1, Comparative Example 1 is different in that this comparative example lacks 4A zeolite, and the rest is the same.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 1 is that this comparative example lacks modified nano titanium dioxide 1, and the rest is the same.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that this comparative example lacks modified basic magnesium sulfate whiskers, and the rest is the same.

[0093] Comparative Example 4

[0094] Compared with Example 1, the difference between this comparative example and Example 1 is that this comparative example lacks 4A zeolite, modified nano titanium dioxide 1, and modified basic magnesium sulfate whisker, and the rest is the same.

[0095] Comparative Example 5

[0096] Compared with Example 1, this comparative example is different in that this comparative example lacks a compatibilizer, and the rest is the same.

[0097] Table 1

[0098]

[0099] Table 2

[0100]

[0101] Performance Test:

[0102] (1) Thermal stability test: According to GB / T 2917.1-2002 standard, the Congo red method was used to test the stabilization time of the sheets in the above embodiments and comparative examples, wherein the stabilization time is the time required for the test paper to change from red to red. The test temperature is 180°C. The results are shown in Table 3. The longer the stabilization time, the better the thermal stability of the material.

[0103] (2) Light aging performance test: The samples in the embodiments and comparative examples were placed in a UV aging box and artificially accelerated by weathering for 500 hours. The yellowing index of the sheet before and after aging was compared with a colorimeter, and then the yellowing index change rate was calculated. The specific formula for the yellowing index change rate is: RYI (%) = (Y1-Y0) / Y0*100, where RYI is the yellowing index change rate, Y0 is the yellowing index of the sample without light aging, and Y1 is the yellowing index of the sample after light aging. The yellowing index change rates in the embodiments and comparative examples of the present invention are shown in Table 3. The smaller the yellowing index change rate, the better the light stability.

[0104] Its ability to resist light and heat (environmental) aging can be verified through thermal stability and light aging performance tests.

[0105] (3) The tensile strength of the sheet was tested according to the standard of GB / T1040-2006-2. The results are shown in Table 3. Among them, the tensile strength is between 34-45 MPa, and the material is more suitable for application in medical devices.

[0106] Table 3

[0107]

[0108] It can be seen from the above embodiments that the PVC material of the present invention has good thermal stability, light aging resistance, and mechanical properties, and can further expand the application scenarios of this type of PVC material.

[0109] It can be seen from Example 1 and Comparative Examples 1-4 that when any one of 4A zeolite, nano titanium dioxide and basic magnesium sulfate whisker is added to the system, the thermal stability and light resistance stability are slightly increased, but when the three are added together, the thermal stability and light resistance stability are significantly increased, and at the same time, the tensile strength does not decrease significantly; wherein, 4A zeolite has a porous structure and is weakly alkaline, which can significantly neutralize and absorb HCl in the system; nano titanium dioxide has an absorption effect on ultraviolet light, and it is a nanostructure with a high specific surface energy, which has a certain adsorption effect on free radicals, HCl and other substances therein, and can significantly inhibit the decomposition of PVC as a whole; basic magnesium sulfate whisker is weakly alkaline and has a fibrous structure, which can neutralize HCl, and its fibrous structure can strengthen and toughen; it may be that nano titanium dioxide, 4A zeolite and basic magnesium sulfate whisker are synergistically interspersed in the PVC matrix to form a specific skeleton structure, which can not only synergistically improve the light and thermal stability of the material, but also will not cause a significant decrease in the toughness and strength of the material, and can still maintain good mechanical properties.

[0110] Compared with Example 1, the difference between Example 3-4 is that the total weight of the modified basic magnesium sulfate whisker and the modified nano titanium dioxide is the same, but the mass ratio of the modified basic magnesium sulfate whisker and the modified nano titanium dioxide is different. It can be found that the mass ratio of the modified basic magnesium sulfate whisker and the modified nano titanium dioxide affects the mutual coordination effect of the nano titanium dioxide, 4A zeolite, and basic magnesium sulfate whisker in the system, thereby affecting the photothermal stability and tensile strength of the material. The inventors of the present invention found that when the mass ratio of the modified basic magnesium sulfate whisker and the modified nano titanium dioxide is (0.4-1.2): (1-1.8), the material of the present invention has relatively better anti-aging performance and tensile strength. In addition, it can be seen from Examples 1 and 5-6 that the total weight of the modified basic magnesium sulfate whisker and the modified nano titanium dioxide also has a certain effect on the stability and tensile strength of the system. The present invention selects the appropriate weight of basic magnesium sulfate whisker and nano titanium dioxide to comprehensively achieve good anti-aging and tensile strength.

[0111] It can be seen from Examples 7-8 that the average particle size of nano-titanium dioxide affects the effect of its dispersion in the matrix and interspersed in the skeleton structure formed by 4A zeolite and basic magnesium sulfate whiskers, and thus affects the anti-aging effect and tensile strength of the material. The inventors of the present invention have found that when the average particle size of nano-titanium dioxide is 150-900nm, good anti-aging and tensile strength can be comprehensively achieved.

[0112] It can be seen from Examples 1, 2 and 9-10 that when the PVC matrix is ​​grafted with PMMA, its tensile strength and anti-aging properties can be significantly improved; and when both nano-titanium dioxide and basic magnesium sulfate whiskers are grafted with PMMA, the compatibility of the nano-titanium dioxide and basic magnesium sulfate whiskers with the matrix can be improved, which not only improves the anti-aging properties of the material to a certain extent, but also enables the material to maintain a better tensile strength.

[0113] It can be seen from Examples 1 and 11-12 that the weight of 4A zeolite has a certain influence on the anti-aging and tensile strength of the material. In the system of the present invention, the weight of 4A zeolite can be selected to be 0.5-5 parts. Too little weight will have little effect on improving the anti-aging performance of the material, and too much weight will significantly reduce the tensile strength of the material.

[0114] It can be seen from Examples 1, 13-14 and Comparative Example 5 that the compatibilizer can significantly improve the compatibility between components in the system and the coordination effect between the components, which not only increases the anti-aging performance of the material to a certain extent, but also significantly improves the tensile strength of the material.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An anti-aging PVC material, characterized in that: The composition comprises the following components in parts by weight: 100 parts of PMMA-grafted PVC, 3-20 parts of plasticizer, 2-5 parts of stabilizer, 0.5-5 parts of 4A zeolite, 1-3 parts of PMMA-modified nano titanium dioxide, 0.1-1.5 parts of basic magnesium sulfate whisker or PMMA-modified basic magnesium sulfate whisker, 0.2-2 parts of compatibilizer, and 0-5 parts of other additives; the average particle size of the nano titanium dioxide in the PMMA-modified nano titanium dioxide is 100-500nm; the compatibilizer is a maleic anhydride-grafted compatibilizer.

2. The anti-aging PVC material according to claim 1, characterized in that: The grafting rate of PMMA in the PMMA-grafted PVC is 1-10 wt.%.

3. The anti-aging PVC material according to claim 1, characterized in that: The mass ratio of the PMMA-modified nano-titanium dioxide to the PMMA-modified basic magnesium sulfate whisker is (1-1.8): (0.4-1.2).

4. The anti-aging PVC material according to claim 1, characterized in that: The preparation method of PMMA-modified nano titanium dioxide comprises the following steps: (1) immersing nano titanium dioxide in an aqueous solution of cycloalkyl imidazoline quaternary ammonium salt and performing a surface modification reaction at 100-120° C. to obtain surface-modified nano titanium dioxide; (2) The surface-modified nano-titanium dioxide, methyl methacrylate and methyl vinyl ketone are reacted under ultraviolet light to obtain PMMA-modified nano-titanium dioxide.

5. The anti-aging PVC material according to claim 1, characterized in that: The preparation method of the PMMA-modified basic magnesium sulfate whisker comprises the following steps: (1) drying the basic magnesium sulfate whiskers, grinding them, and dispersing them in water to obtain a basic magnesium sulfate whisker slurry; (2) dissolving PMMA and calcium stearate in anhydrous ethanol and toluene solvents; Then, the basic magnesium sulfate whisker slurry is added under light-proof conditions to react, and then filtered and dried to obtain PMMA-modified basic magnesium sulfate whiskers.

6. The anti-aging PVC material according to claim 1, characterized in that: Include at least one of the following: The stabilizer includes at least one of an organic tin stabilizer, an organic zinc stabilizer, and an organic calcium stabilizer; The plasticizer includes at least one of phthalate and epoxy plasticizer; The other auxiliary agents include the following components in parts by weight: 0.1-2 parts of colorant, 0.1-5 parts of flame retardant, and 0.1-3 parts of lubricant.

7. A method for preparing the anti-aging PVC material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing, melting and kneading, and extruding the raw materials in sequence to obtain the anti-aging PVC material.

8. Use of the anti-aging PVC material according to any one of claims 1 to 6 in the preparation of medical devices.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide special for color master batch

    CN107400381A

  • Modified calcium sulfate whisker filled rigid polyvinyl chloride drainage pipe and preparation method thereof

    CN111154201A

  • HDPE / PVC blended modified material

    CN113754969A